Basilar artery occlusion: Prognostic signs of severity on computed tomography. Issue 7 (July 2015) - Poletti, Pierre-Alexandre; Pereira, Vitor Mendes; Lovblad, Karl-Olof; Canel, Lucie; Sztajzel, Roman; Becker, Minerva; Perneger, Thomas; Platon, Alexandra
Highlights: The main CT signs associated with basilar artery occlusion were analyzed. CT sign of acute ischemic lesion is significantly associated with a bad outcome. The site of the basilar artery occlusion is not associated to the patients' outcome. Abstract: Purpose: To determine the computed tomography (CT) signs that are predictive of the clinical outcome of basilar artery occlusion (BAO). Materials and methods: The study population consisted in 37 patients (14 women, 23 men, mean age: 63 years), admitted with onset of neurological deficit, starting 1–72 h prior to admission, who were diagnosed with BAO on the basis of a CT examination with intravenous contrast agent. The following signs were collected on CT scans performed on admission: clot density on noncontrast images, clot length, and clot location, as well as the presence of acute ischemic lesions. The results were compared against the modified Rankin Scale (mRS) score of patients at 3 months, favorable clinical outcome being defined as a mRS score ≤3. Results: The clinical outcome was favorable in 13 (35%) of the 37 patients and unfavorable in 24 (65%). Signs of acute ischemia were visible in 13 of the 24 patients with unfavorable outcome but in none of the 13 patients with favorable outcome ( p < 0.001). None of the other CT signs analyzed were significantly correlated with clinical prognosis. Conclusion: Of all the CT signs analyzed, only the presence of signs of acute ischemia on the admission CT of patients with BAO was associated with poor prognosis.